A Religião of the Floresta: apontamentos sociológicos em direção a uma genealogia do SantoDaime e seu processo de diáspora - Glauber Loures de Assis (2017)
In the 21st century, several religious practices born in Brazil have been exported internationally, in a broad movement known as the diaspora of Brazilian religions. Among them are Neo-Pentecostalism, Afro-Brazilian religions, União do Vegetal, the Catholic Charismatic Renewal and Santo Daime. Although this broader context is important for understanding the expansion of these groups, there are also particularities in the diasporic movement of each of these religious forms. Through a comparative approach, this thesis focuses on the specific case of the Santo Daime religion, seeking to insert it into broader sociological discussions and atthe same time drawing attention to its particularities and idiosyncrasies. For this purpose, we propose the construction of a genealogy of the Santo Daime diaspora, based on the case study of ICEFLU, the pioneer group in the daimist diaspora and to this day the largest and most global institution of this religion. The Santo Daime began to be configured from the 1930s on the territory of Acre, with a strongly regionalist and family character, congregating at that time mainly black people and caboclos of low schooling and precarious financial conditions. Today, Santo Daime presents itself as the "Religion of the Forest", being present in at least 43 countries of all the continents inhabited and congregating some thousands of people, among Brazilians and foreigners, especially high schooling people of the urban middle classes. Our genealogical effort seeks to open the "black box" of daimist history and to analyze how the diaspora of that religion is possible and how it is constructed. We will therefore perceive that although the Santo Daime is naturalized as a relatively homogeneous group by common sense and by a good part of its members, it is polyphonic, polysemic and polycentric, constituting a field of struggles and disputes of meaning and agency and dialoguing with various actors and external processes, being continuously influenced by them. Therefore, we realize that the development of the Santo Daime and its expansion do not travel a straight path. Instead, it is the result of a tortuous historical process, permeated by conflicts, power disputes and alliances between multiple actors, becoming a complex and emergent phenomenon. We will see that this movement is driven by a "primordial tension" existing within the Daime religion, where a centrifugal, expansionist force ("from the forest to the world") coexists with a centripetal, reflexive one ("from the world to the forest"). In this sense, the daimist diaspora produce not only international repercussions on the lives of its members living in urban centers, but also strong reflexive effects on the "traditional" nuclei of the Santo Daime in the Amazon.With this genealogical effort, we hope to stimulate and pave the way for new research on daimist religiosity and the themes that involve it, such as the ritual use of psychoactive substances and their controversies, the construction and negotiation of religious identities, and the diaspora of Brazilian religions.